California State College at Hayward Summer Quarter Summer Session 1965 - California State College, Hayward:::::: (1965)
This contains a list of courses offered and other relevant information for the 1965 summer quarter (June 15 to August 31) and the summer session (June 21 to July 30) at California State College at Hayward.